Influence of Epoxy/Nanosilica on Mechanical Performance of Hemp/Kevlar Fiber Reinforced Hybrid Composite with an Ultrasonic Frequency - G. Velmurugan; L. Natrayan; Yenda Srinivasa Rao; Piyush Gaur; S. Sekar; Rohinikumar Chebolu; Pravin P. Patil; Prabhu Paramasivam (Adsorption Science & Technology)
Ultrasonic vibration was employed in blending the nanosilica into epoxy resin to manufacture hemp/kevlar/nanosilica-based epoxy composites, with an ultrasonic occurrence of 20 kHz and a 900 W capacity of power. An ultrasonic probe was utilized to ensure the consistent dispersion of the nanoparticles in the epoxy. The mechanical characteristics of hemp/kevlar fiber reinforced with epoxy/nanosilica in a mat form have been studied. Hand layup procedures were used to create these composites, including varying weight % of nanosilica and variable fiber stacking sequencing. The different weight % are 3, 6, and 9, and the stacking sequences are B, C, and D. The effectiveness of ultrasonic irradiation on mechanical characteristics was investigated and related. The inclusion of 6 wt.% of SiO2 to the B type resulted in a 25% rise in tension and a 37% in bending. The addition of 6 wt.% silica to the C-type hybridization nanocomposite results in a 34% rise in tension and a 38% rise in bending. Extreme tension behavior is attained at 6 wt.% SiO2 with epoxy with the B type piling order, and extreme bending behavior is obtained at 6 wt.% SiO2 with the C type piling order. A B-type model composite with a 6-wt.% SiO2 addition performed better in hygroscopic than A, C, and D type model composites. An SEM is utilized to observe the microstructure of shattered materials.